Pengaruh variasi lama fermentasi terhadap kualitas kimia bokashi berbasis limbah peternakan dan pertanian - HIRONIMUS NANA; Edelnia Kristina Bere; Gomera Bouk (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2026)
This study aims to determine the effect of variations in fermentation time on the chemical properties of bokashi and to compare whether the resulting bokashi meets the quality standards of the Indonesian National Standard (SNI) for Solid Organic Fertiliser. This study was conducted at the Kupang Animal Husbandry Training Centre and analysed in the Soil Chemistry Laboratory of Nusa Cendana University. The materials used in this study consisted of livestock waste and agricultural waste fermented using EM4 and molasses. The study used a completely randomised design (CRD) with 3 treatments and 5 replications, where each replication consisted of 15 kg of solid material with the same material composition. The treatments tested were fermentation time consisting of P1 (7 days), P2 (14 days) and P3 (21 days). The research data were analysed using analysis of variance (ANOVA), followed by the Least Significant Difference (LSD) test and the Games-Howell test. The results showed that different variations in fermentation time had a significant effect (P < 0.05) on the chemical quality of bokashi. Treatment P3 (21 days of fermentation) gave the most balanced chemical quality, resulting in the optimal organic carbon content at 25.65%, the highest nitrogen increase with N 2.39%, and a significantly decreased C/N ratio to the lowest level of 10.74. Furthermore, it also increased P to 0.67%, K to 0.86%, and maintained a neutral pH of 7.78. The chemical quality of bokashi produced from all treatments has met the quality standards of SNI 7763:2024 Solid Organic Fertilizer. It can be concluded that variations in fermentation time affect the chemical content of bokashi based on livestock and agricultural waste and can be used to obtain better bokashi quality.